Spatial variation in abundance of the junin virus hosts in endemic and nonendemic Argentine haemorrhagic fever zones - Polop, Jaime J (2007)
Fil: Polop, Jaime J. Departamento de Ciencias Naturales, Universidad Nacional de Río Cuarto; Argentina.